The Image of the Kurds in The Arab Literary Sources - Fattah, Fawzia Y.; Salim, Lolaf M. (Humanities Journal of University of Zakho, 2014)
The research highlights the image of the Kurds in the Arab literary sources, and the image of the princes of the Kurds in particular, and shows the bias of poets and writers along with the army of the Caliph and his allies in their poems as the ruling power. On the other hand, the elite tried to approach power through poems and other literary texts. From this, the literary books referred to some of the Kurdish princes and their combat role. The Kurds also had a great contribution in helping others in times of need and resorting to the strongholds and countries of the Kurds in adversity. The research center also on the characteristics of the Kurds, which is courage, as several examples appear that show the advantage of the Kurds and their princes.